Energy landscape in Mauritius. (June 2017) - Surroop, Dinesh; Raghoo, Pravesh
Abstract: Located in the Indian Ocean, Mauritius is among the Small Island Developing States (SIDS), entirely reliant on coal, petroleum and some locally available renewable energy sources to satisfy energy needs. 22.7% of the electricity is generated by biomass, solar, landfill gas and hydro and the remaining by fossil fuels. Even with continual oil price volatilities and specific economic, social and environmental vulnerabilities compared to continental areas, Mauritius has successfully provided 100% electricity to all its residents. However, with a growth in population and economy, Mauritius faces a crucial challenge to supply more electrical power to all requiring sectors. Renewable energy appears to be the most effective solution to cater for the increase in electricity demand but there are still huge challenges to overcome for massive deployment of more renewable energy. In this context, this paper reviews the current electricity industry and fuel sources for electricity production in Mauritius. It also describes future energy policies for more renewable energy integration within the energy mix by 2025.